Aplicativo móvel para prevenção e classificação de úlceras por pressão - Tibes, Chris Mayara dos Santos (Universidade Federal de São Carlos, 2015)
The popularity of mobile devices has been considered by many the technological revolution with the greatest impact in recent years. Thus, the application development (software) for mobile devices provides an effective way of providing content and reaches the desired audience. The use of computational tools in healthcare is becoming increasingly widespread. Currently, one of the topics more addressed in the health field is related to the patient safety. The Brazilian Ministry of Health and ANVISA launched the Ordinance Nº 529 of April 1st 2013, which established the National Patient Safety Program. This ordinance aims to reduce adverse events in health care, including reducing the incidence of pressure ulcers. Prevention and treatment of pressure ulcers are mainly related to the nursing team and in many health institutions the incidence of pressure ulcers is used as an indicator of care quality. In this sense, it is fundamental equip professionals with resources that enable them to predict the patient's risk of developing pressure ulcers, support them to classify this type of injury and help them forward for decision making in the implementation of care adequate to prevent and/or treat this type of injury. Information technology can help these professionals. In addition to being able to store and compress a large volume of information, this type of tool is highly portable, adaptable and broad scope. In order to assist nurses in their professional practice, this research aimed to develop a mobile application prototype to assist in the prevention and classification process of pressure ulcers. The developed application is able to calculate the risk assessment, suggest cares for prevention and/or treatment of pressure ulcers, as well as to classify existing ulcers. The technical and functional quality of the application was evaluated by computing and nursing specialists and was considered adequate in question as functionality, reliability, usability, efficiency, maintainability and portability. As future work, it is proposed to evaluate the developed application in its ability of reducing the ulcer pressure incidence with users in care practice.
Keywords: Enfermagem; Informática em saúde; Serviços de saúde - medidas de segurança; Software - desenvolvimento; Nursing; Nursing informatics; Software; CIENCIAS DA SAUDE::ENFERMAGEM